Hubungan Pelayanan Tenaga Kesehatan dengan Kepuasan Klien di Ruang Rawat Inap Rumah Sakit - Chairulfalah, Achmad Machron; Riyanto, Dwi Agung (Faletehan Health Journal, 2024)
Strategic efforts to accelerate the improvement of public health status must be owned by health facilities. The level of patient satisfaction closely relates to the service provided by health workers in hospital institutions. The ability to provide optimal service, to improve the quality of service to community, and to consider client satisfaction factors must be prioritized by health workers. This research aimed to determine the relationship between health worker services and the level of satisfaction of inpatient clients at Kencana Serang Hospital in 2022. It used a correlation test and a cross-sectional design. The research population was inpatients at Kencana Serang Hospital and the sample size was 100 respondents. The results of the data analysis showed that there was a close relationship between service providers and patient satisfaction factors. Hospital management should attempt to improve the aspects of monitoring function of health workers performance evaluation in providing services to clients.